2021
DOI: 10.1200/op.20.00904
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Productivity Impact of Acute Myeloid Leukemia in Australia Between 2020 and 2029, Using a Novel Work Utility Measure: The Productivity-Adjusted Life Year (PALY)

Abstract: PURPOSE: Acute myeloid leukemia (AML) is a rare hematologic malignancy accounting for 0.8% of new cancer diagnoses in Australia. High mortality and morbidity affect work productivity through workforce dropout and premature death. This study sought to estimate the productivity loss attributable to AML in the Australian population over 10 years and to estimate the costs of this productivity loss. Productivity was measured using productivity-adjusted life years (PALYs), a similar concept to quality-adjusted life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The impact of BC screening on life-years, PALYs, and gross domestic product (GDP) over the subsequent 5 years was examined using dynamic life table modeling [29] in female patients aged 40 to 64 years diagnosed with BC in Japan in 2019. This target age range was chosen because the target age for BC screening is 40 and above and the current full-time employment period in companies ends at age 65 in Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of BC screening on life-years, PALYs, and gross domestic product (GDP) over the subsequent 5 years was examined using dynamic life table modeling [29] in female patients aged 40 to 64 years diagnosed with BC in Japan in 2019. This target age range was chosen because the target age for BC screening is 40 and above and the current full-time employment period in companies ends at age 65 in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…PA LY s are calculated by multiplying the 'productivity index' from 0 (not productive at all) to 1 (fully productive) by the number of life-years lived [24]. Several studies have reported work productivity using PALY, including studies on osteoarthritis, type 2 diabetes, hypertension, depression, and acute myeloid leukemia [25][26][27][28][29]. The novelty of the current study lies in the use of PALY to calculate the benefits of increased screening-detected BC and work productivity from an economic perspective in Japan.…”
Section: Introductionmentioning
confidence: 99%